2008
DOI: 10.1163/156853708x358209
|View full text |Cite
|
Sign up to set email alerts
|

Holism in a European Cultural Context: Differences in Cognitive Style between Central and East Europeans and Westerners

Abstract: Central and East Europeans have a great deal in common, both historically and culturally, with West Europeans and North Americans, but tend to be more interdependent. Interdependence has been shown to be linked to holistic cognition. East Asians are more interdependent than Americans and are more holistic. If interdependence causes holism, we would expect Central and East Europeans to be more holistic than West Europeans and North Americans. In two studies we found evidence that Central and East Europeans are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 19 publications
4
60
0
Order By: Relevance
“…Russians are more interdependent than Americans (Grossmann, 2009; Matsumoto, Takeuchi, Andayani, Kouznetsova, & Krupp, 1998) and are more holistic in terms of categorization, attribution, visual attention, and reasoning about change (Grossmann, 2009). Similarly, Croats are more interdependent than Americans (Šverko, 1995) and show more holistic patterns of cognition in terms of categorization and visual attention (Varnum, Grossmann, Katunar, Nisbett, & Kitayama, 2008). Recent evidence suggests that similar differences exist within Europe.…”
Section: Cross-cultural Comparisonsmentioning
confidence: 99%
“…Russians are more interdependent than Americans (Grossmann, 2009; Matsumoto, Takeuchi, Andayani, Kouznetsova, & Krupp, 1998) and are more holistic in terms of categorization, attribution, visual attention, and reasoning about change (Grossmann, 2009). Similarly, Croats are more interdependent than Americans (Šverko, 1995) and show more holistic patterns of cognition in terms of categorization and visual attention (Varnum, Grossmann, Katunar, Nisbett, & Kitayama, 2008). Recent evidence suggests that similar differences exist within Europe.…”
Section: Cross-cultural Comparisonsmentioning
confidence: 99%
“…Previous research suggests that cultural differences exist in cognitive functioning between countries from Eastern and Western Europe (Varnum et al, 2008). Therefore, the authors anticipate that such differences will also be found in the current research project.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…Independent societies tend to be more analytic while interdependent societies are more holistic (Nisbett and Miyamoto, 2005). This indicates that Eastern Europeans have a more holistic cognitive style compared to Western Europeans, who are more analytical (Varnum et al, 2008). Considering the aforementioned results, this study aims to further analyze whether intercultural differences in cognitive functioning exist not only between the countries from Eastern and Western Europe but also within Eastern European countries.…”
Section: Introductionmentioning
confidence: 99%
“…Foard and Kemler (1984) introduce analytical-holistic modus or continuum to confirm that some countries are not purely analytical or holistic but mixed or transitional. The following countries can be placed from analytic to holistic on a continuum: The USA -Western Europe -Eastern and Central Europe (including Russia) -South East Asia (Varnum et al, 2008).…”
Section: Germans Americans Frenchmentioning
confidence: 99%
“…Henrich et al (2010) conclude that a mature individual uses both cognitive systems (rationalism and intuition); however, a given culture uses more often one system at the expense of another when faced with some kind of decision-making problem. Holistics cultures are connected with collectivism while analytic cultures with individualism (Varnum et al, 2008;Uskul et al, 2008).…”
Section: Germans Americans Frenchmentioning
confidence: 99%